A Natural Transporter of Silicon and Carbon: Conversion of Rice Husks to Silicon Carbide or Carbon‐Silicon Hybrid for Lithium‐Ion Battery Anodes via a Molten Salt Electrolysis Approach. Issue 12 (12th September 2019) - Zhao, Zhuqing; Xie, Hongwei; Qu, Jiakang; Zhao, Haijia; Ma, Qiang; Xing, Pengfei; Song, Qiushi; Wang, Dihua; Yin, Huayi
Abstract: The use of environment‐benign and earth‐abundant silicon (Si) and carbon (C) is the quest to meet the ever‐increasing Li‐ion battery (LIB) market. Unlike the traditional way of either extracting C or Si, here, we report a molten salt electrolysis approach to controllably extract both C and Si (e. g., C−SiC or C−Si composites) from rice husks (RHs). The RHs are the natural transporter that captures carbon dioxide (CO2 ) from the air and silicic acid (H4 SiO4 ) from the soil, thus supplying abundant, sustainable, and hierarchically porous C−SiO2 composite feedstocks. In molten CaCl2, carbonized RHs (C−RHs) can be electrochemically reduced to the C−SiC composite that delivers a gravimetrical capacity of over 1000 mA h g −1 at 1000 mA g −1 after 400 cycles. In molten NaCl−KCl−MgCl2, the C−RHs can be electrochemically reduced to C−Si composite that delivers a gravimetrical capacity of 926 mA h g −1 at 500 mA g −1 after 100 cycles. The electrolytic products can be altered by the component of molten salt as well as by adjusting the applied cell voltage. Overall, we employ the photosynthesis of plants to harvest Si and C from nature and, subsequently, the molten salt electrolysis approach to preparing C−SiC and C−Si composites for low‐cost and sustainable LIB anodes. Abstract : Putting waste to good use: Both C−SiC and C−Si composites are synthesized from the rice husks via a molten salt electrolysis approach, and the constituents and structures of the electrolytic products were engineered by manipulating the cations of the molten salts, carbonization procedures, as well as the electrochemical variables. The obtained C−SiC and C−Si anodes exhibit excellent electrochemical performances.